Pemberdayaan Perempuan Kelompok Srikandi Melalui Pelatihan Pembuatan Aneka Sambal di Desa Jengkol Kabupaten Wonosobo - Laela Uswatun Hasanah; Sungkowo Edy Mulyono (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
The Srikandi group is a group of women who have concerns about the Prevention of Trafficking in Persons (TPPO). Therefore, the Kita Institute packages TPPO as a strengthening of the women's economy, namely by empowering the women of the Srikandi Group through training in making various chili sauces. This study aims to describe the implementation process, success, supporting factors and inhibiting factors. This study uses a qualitative approach with research subjects including Kita Institute managers, Srikandi Group Managers, and Srikandi Group Members. The data validity technique uses source triangulation with data analysis technique using data collection, reduction, presentation, and conclusion drawn. The results of the research that have been carried out show that 1) The process of implementing women's empowerment in the Srikandi Group consists of three stages. The first stage is awareness through socialization and motivation. Then, the ability transformation stage is to increase knowledge and skills in making various chili sauces. The last stage is capacity improvement, where the women of the Srikandi group have been able to produce various chili sauces independently. 2) Women's empowerment of the Srikandi group succeeded in producing a variety of quality chili sauce with a durability of two months and increasing income 3) Supporting factors for empowerment are the availability of human resources, natural resources, infrastructure, high motivation of participants, female participation, and work partners. Meanwhile, the factors that inhibit empowerment are difficulties in adjusting the time and lack of confidence of Srikandi group women to start their own business. Keywords: , ,